A Study of Work Satisfaction, Burnout and other Work-Related Variables Among Hungarian Educators - Pikó, Bettina F.; Mihálka, Mária (European Journal of Mental Health, 2017)
The main goal of the present study was to investigate, based on the Job Demands-Resources Model, a set of work-related variables as possible correlates (either as job demands or resources) of work satisfaction in a sample of Hungarian educators (N = 2,068, aged between 23-74 years, mean = 48.1 and S.D. = 8.9; 83% females). Results report that in this sample of Hungarian educators, their work satisfaction is closely related to the presence of burnout (particularly emotional exhaustion) and it is also influenced by role conflicts and role ambiguity in their workplace; whereas work-family conflict and work time demands do not play a role. On the other hand, educators- work satisfaction may be protected by certain job resources such as satisfaction with professional prestige, work social support and work involvement. Satisfaction with salary and work policy was not significant. Findings suggest that interventions at both individual and organisational level should be necessary, e.g. learning effective coping techniques to prevent burnout and increase work satisfaction well before the start of an educator-s career. The organisational interventions should strengthen job resources and eliminate/decrease job demands.